Guide to Identifying and Controlling Postharvest Tomato Diseases in Florida - Jerry A. Bartz; Gary E. Vallad; Steven A. Sargent (EDIS, 2020)
Pathogens are present in all tomato production areas and are most numerous when the weather becomes warm and wet. Movement of weather fronts or tropical storms through production areas can also affect the susceptibility of tomato fruit to decay. Fruit decays can be minimized by the employment of strict sanitation measures along with careful handling. This bulletin is designed to supplement field scouting and identification guides by